2010
DOI: 10.1016/j.neuroscience.2009.12.062
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin enhances hippocampal long-term potentiation in C57BL/6 mice

Abstract: Statins inhibit 3-hydroxy-3-methylglutaryl CoA reductase (HMG-CoA), the rate-limiting enzyme in the cholesterol biosynthetic pathway, and they are widely used to control plasma cholesterol levels and prevent cardiovascular disease. However, emerging evidence indicates that the beneficial effects of statins extend to the central nervous system. Statins have been shown to improve the outcome of stroke and traumatic brain injury, and statin use has been associated with a reduced prevalence of Alzheimer's disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 49 publications
8
52
3
Order By: Relevance
“…Strong depression of basal synaptic transmission and LTP impairment has been observed upon cholesterol reduction with cyclodextrin (Frank et al, 2008). In contrast, LTP enhancement and no effect on basal transmission were reported with a statin inhibitor of cholesterol biosynthesis (Mans et al, 2010). However, the opposite effect (LTP impairment) was observed using a different statin (Kotti et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Strong depression of basal synaptic transmission and LTP impairment has been observed upon cholesterol reduction with cyclodextrin (Frank et al, 2008). In contrast, LTP enhancement and no effect on basal transmission were reported with a statin inhibitor of cholesterol biosynthesis (Mans et al, 2010). However, the opposite effect (LTP impairment) was observed using a different statin (Kotti et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in concurrence with reports from the present study and another laboratory ) and the dose-dependent effect is seen with HSP treatment. The improvement in spatial memory as measured by the two different maze tasks is dependent on hippocampus-mediated learning and memory, which is related to the NMDA receptor/Ca 2 þ influx signalling pathway (Obeid & Herrmann 2006).Recent reports have revealed that flavonoids and other small molecules or drugs affect long-term potentiation and consequently, memory and cognitive performance through their interactions with these signalling pathways (Maher 2008;Mans et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, chronic simvastatin treatment increased brain levels of total and phosphorylated Akt (P-Akt) in WT mice with enhanced learning and memory performance (Li et al, 2006). In hippocampal slices from WT mice, prolonged simvastatin treatment increased P-Akt in the CA1 area concomitantly with improved LTP at CA3-CA1 synapses, an effect suppressed by inhibition of Akt phosphorylation (Mans et al, 2010). Together, these findings support that simvastatin rescued memory in adult APP mice by restoring the ability of hippocampal CA1 neurons to respond to synaptic input, possibly by restoring the PI3K/Akt 3 P-CREB 3 Egr-1/cFos signaling cascade that is crucial for spatial memory.…”
Section: Discussionmentioning
confidence: 99%